Telehealth in Heart Failure Management: A Scoping Review - Felipe Montes Pena; Lyana Reis de Moura; Ingrid Lopes da Silveira Vianna Corrêa; Tatiana Cabral da Silva Ramos; Renata Flávia Abreu da Silva; Cristiane Helena Gallasch; Raphael Chança; Magda Guimarães de Araujo Faria (Telemedicine and e-Health, 2026)
Introduction: Heart failure (HF) entails high morbidity, mortality, and health care costs. This scoping review maps and describes telehealth interventions for adult HF management, summarizing modalities, contexts, and reported outcomes (morbidity, mortality, and hospitalizations), and identifying evidence gaps, implementation challenges, and future trends. Our review question was: Which telemedicine interventions have been used in adult HF management, in which contexts, and what outcomes are reported for morbidity, mortality, and hospitalizations? Methods: We searched four electronic databases (MEDLINE via PubMed, Latin American and Caribbean Health Sciences Literature, Cumulative Index to Nursing and Allied Health Literature, and Scopus) and gray literature (DataBase of Theses and Dissertations, Brazil) through December 2023, using a Population, Concept, Context framework. Two independent reviewers screened and extracted data; discrepancies were resolved by a third reviewer. Results: Of 1,122 records, 81 studies were included. Evidence spans 12 thematic areas covering telemonitoring modalities, adherence, clinical indicators, early detection, symptom management, communication, satisfaction, cost considerations, comparative perspectives, public health contributions, and future trends. Reported outcomes were heterogeneous across study designs and settings. Evidence on effectiveness is mixed across modalities and settings. Signals of benefit appear in integrated, protocolized telemonitoring programs—particularly for reducing readmissions in selected contexts—while other modalities show neutral effects. Key gaps relate to standardization, data integration, and long-term sustainability. Conclusion: Telehealth is widely applied in HF care with diverse implementations; further rigorous and standardized evaluations are needed to clarify effectiveness across modalities and settings.